Prostheses, cyborgs and cyberspace - the cyberpunk trinity - Sever, Staša (ELOPE (Ljubljana), 2013)
This article will explore three elements that have collectively become the sine qua non of our lives: prostheses, cyborgs and cyberspace. The main concern of the article is to show the close connection between the technology-saturated reality of today and the literature of cyberpunk as the prototypical representative of merging the human and the technological. This will enable us to explore the interaction between literature and reality in the formation of the cyborg of today.
Keywords: kiberpank; kiberprostor; kiborg; književnost; literature; proteze